Cochrane Database of Systematic Reviews 2011
DOI: 10.1002/14651858.cd001478.pub4
|View full text |Cite
|
Sign up to set email alerts
|

Acellular vaccines for preventing whooping cough in children

Abstract: Background Routine use of whole-cell pertussis (wP) vaccines was suspended in some countries in the 1970s and 1980s because of concerns about adverse e ects. Following this action, there was a resurgence of whooping cough. Acellular pertussis (aP) vaccines, containing purified or recombinant Bordetella pertussis (B. pertussis) antigens, were developed in the hope that they would be as e ective, but less reactogenic than the whole-cell vaccines. This is an update of a Cochrane review first published in 1999, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0
4

Year Published

2012
2012
2014
2014

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 82 publications
0
35
0
4
Order By: Relevance
“…The resurgence began during the wP vaccine era, but the pace has quickened since aP vaccines were recommended for all primary and booster doses (11). This correlation has led many to hypothesize that aP vaccines are less effective on a population scale than the wP vaccines they replaced (10,12,13). Consistent with this notion, several recent observational studies concluded that children primed with aP vaccine had a twofold to fivefold greater risk of pertussis diagnosis compared with wP-primed children (19)(20)(21)(22).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The resurgence began during the wP vaccine era, but the pace has quickened since aP vaccines were recommended for all primary and booster doses (11). This correlation has led many to hypothesize that aP vaccines are less effective on a population scale than the wP vaccines they replaced (10,12,13). Consistent with this notion, several recent observational studies concluded that children primed with aP vaccine had a twofold to fivefold greater risk of pertussis diagnosis compared with wP-primed children (19)(20)(21)(22).…”
Section: Discussionmentioning
confidence: 99%
“…Observational studies suggest that asymptomatic pertussis can occur in vaccinated children and adults based on PCR or serological data (34,35). However, during the aP vaccine trials, participants were not screened for B. pertussis infection unless they presented with pertussis-like symptoms and at least 7-21 d cough (12). Therefore, no experimental data exist on whether vaccination prevents B. pertussis colonization or transmission in humans.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Re-introduction of wP would risk increasing pertussis incidence as a result of lower vaccine uptake. The recent Cochrane review found non-completion of the primary series due to adverse events is significantly lower for aP than wP vaccines (120). In such a circumstance, declining vaccine coverage may outweigh the advantage of increased effectiveness of wP.…”
Section: Changes To the Pertussis Vaccination Schedulementioning
confidence: 99%
“…This difference persisted for more than a decade, being evident in pre-epidemic and outbreak periods. A primary course using even a moderately effective DTwP vaccine may be more protective than DTaP (120). In the pre-acellular era, Australia used a locally produced DTwP vaccine with very good to excellent effectiveness (112).…”
Section: Commentmentioning
confidence: 99%